Judicial review of de activity of the public Administration - Burneo, José Antonio (2023)
Public power is not unlimited. Because it has certain limits that come from the very existence of a State of Law, governed in primacy by a constitution, such as magna carta. In this sense, the applicability of resources that serve as a mechanism to prevent the abuse of power of the public administration is crucial for the citizen. Be- cause the violation of rights by excess of power of the  administration, or also by a negligence in its functions, is a probability that cannot be eliminated since its risk of occurrence depends on so many factors that will be evident only in the evolution of life in society. In this way, the law, in general, and administrative law, have formulated different remedies that serve the objectives of protection of the citizen or, failing that, the enforceability of his infringed or infringed rights.